Analisis Pengaruh Consumer Animosity Dan Consumer Ethnocentrism Terhadap Purchase Intention(Studi Empiris Dalam Membeli Produk Asal AS Oleh Mahasiswa FEB di Universitas Muhammadiyah Surakarta) - Firmansya, Abi; , Muhammad SholahuddinS.E. M.Si (2017)
This study aim to analyze the effect of consumer animosity and consumer ethnocentrism on purchase intention. The independent variables consist of consumer animosity and consumer ethnocentrism, meanwhile the dependent variable is purchase intention. The population of this research is the collage students of economic and business faculty of Muhammadiyah University of Surakarta. The technique of the sample collection was convenience sampling method. The samples are taken from 117 collage students, while the research instrument is in the form of questionnaire. The analysis used in this research includes validity test, reliability test, the classical assumption test, multiple liniear regression analysis, t test, F test and the coefficient of determination analysis (R^2), The result of this research show that consumer animosity has an significant and positive effect on purchase intention. Consumer Ethnocentrism not significantly and negatively influences on purchase intention. Simultaneously consumer animosity and consumer ethnocentrism has a influence on purchase intention with the constributions made (R^2) of 1% and the rest is explained by other variables. Keyword: Consumer Animosity, Consumer Ethnocentrism, and Purchase Intention.